Peningkatan Pengetahuan Ibu Balita tentang Pencegahan Stunting melalui Pijat Melongas - Widani Darma Isasih; Baiq Dinda Puspita Ayu; Muhammad Nasir; Lalu Abdul Aziz (CV. Global Cendekia Inti, 2026)
Stunting remains a significant public health problem with long-term impacts on child growth and development. This community service aimed to improve mothers’ knowledge on stunting prevention through the integration of local practice, namely melongas infant massage. The activity was conducted at a primary health center in Lombok Utara involving 20 mothers with toddlers using an educative-participatory approach. The program consisted of preparation, socialization with focus group discussion, practical demonstration, and evaluation stages. Initial assessment showed that 70% of participants had low knowledge regarding stunting. After the intervention, there was a notable improvement, with 75% of participants achieving good knowledge levels. The implementation stage also demonstrated that 85% of participants were able to correctly perform melongas massage techniques. Furthermore, about 80% of participants understood the relationship between nutrition, parenting practices, and child stimulation in preventing stunting. Reflective discussions indicated that most participants felt confident to apply the massage techniques at home. The findings suggest that integrating local wisdom into health education enhances understanding and acceptance among participants. This approach not only improves knowledge but also encourages practical behavior change in stunting prevention. Therefore, melongas infant massage can be considered a contextual and sustainable strategy to support community-based stunting prevention programs.